Identification of Cherry Tomato Volatiles Using Different Electron Ionization Energy Levels - Dalma Radványi; László Csambalik; Dorina Szakál; Attila Gere (Molecules)
A comprehensive analysis of the volatile components of 11 different cherry tomato pastes (Tesco Extra, Orange, Zebra, Yellow, Round Netherland, Mini San Marzano, Spar truss, Tesco Sunstream, Paprikakertész, Mc Dreamy, and Tesco Eat Fresh) commercially available in Hungary was performed. In order to ensure the reliability and accuracy of the measurement, the optimal measurement conditions were first determined. SPME (solid-phase microextraction) fiber coating, cherry tomato paste treatment, and SPME sampling time and temperature were optimized. CAR/PDMS (carboxen/polydimethylsiloxane) fiber coating with a film thickness of 85 µm is suggested at a 60 °C sampling temperature and 30 min extraction time. A total of 64 common compounds was found in the prepared, mashed cherry tomato samples, in which 59 compounds were successfully identified. Besides the already published compounds, new, cherry tomato-related compounds were found, such as 3 methyl 2 butenal, heptenal, Z-4-heptenal, E-2-heptenal, E-carveol, verbenol, limonene oxide, 2-decen-1-ol, Z-4-decen-1-al, caryophyllene oxide, and E,E-2,4-dodecadienal. Supervised and unsupervised classification methods have been used to classify the tomato varieties based on their volatiles, which identified 16 key components that enable the discrimination of the samples with a high accuracy.